Treatment-free survival after discontinuation of immune checkpoint inhibitors in mNSCLC: a systematic review and meta-analysis - Hu, Yue; Liu, Shan; Wang, Lixing; Liu, Yu; Zhang, Duohan; Zhao, Yinlong (Frontiers in Immunology, 2023)
Background Recent research has suggested that patients with metastatic non-small cell lung cancer (mNSCLC) can achieve ongoing response after discontinuation of immune checkpoint inhibitor (ICI), but the best time to discontinue and the factors influencing efficacy remain unknown. Method A systematic search was performed for prospective clinical trials in patients with mNSCLC treated with ICIs published up to July 10, 2022. Eligible studies reported treatment-free survival (TFS) after discontinuation of ICI in partial objective responders. We calculated objective response rate (ORR) and TFS using random-effects models with respective 95% confidence intervals (Cis), and performed subgroup analyses to discuss the specific associations between ORR and TFS and the associated influencing factors. Results Across the 26 cohorts (3833 patients) included, the weighted mean ORR for all patients was 29.30% (95% CI 24.28% to 34.57%), with ICI plus chemotherapy (48.83%, 95% CI 44.36% to 53.30%) significantly higher than monotherapy (23.40%, 95% CI 18.53% to 28.62%). 395 patients were all patients who were complete or partial responders in the study, 194 discontinued ICI treatment, and nearly 35.5% achieved a durable response. No significant differences in TFS were found between subgroups according to the ICI regimen classification. Four cohorts of patients who completed 35 courses of treatment showed high levels of pooled TFS at 6 (80.18%, 95% CI 53.03% to 97.87%) and 12 months (66.98%, 95% CI 46.90% to 84.47%). Three cohorts of patients discontinued ICI treatment due to treatment-related adverse events (TRAEs) with the TFS rates at 6 (76.98%, 95% CI 65.79% to 86.65%) and 12 months (64.79%, 95% CI 50.20% to 78.19%). Conclusion Patients with mNSCLC were able to achieve ongoing responses after discontinuation of ICI. In conclusion, the results of this meta-analysis indicate that different treatment regimens, different drugs or different treatment durations may have an impact on TFS.